The impact of environmental factors, sowing time, and soil conditions on the growth, yield, and resilience of Fagopyrum tataricum and Fagopyrum esculentum in Egyptian agroecosystems - Mohamed M. Hassona; Nahla M. Morsy; Ahmed M. S. Hussein; Hala A. Abd El-Aal (PLoS ONE, 2026)
Background Buckwheat ( Fagopyrum spp.) is a gluten-free pseudocereal with high nutritional and bioactive value, offering the potential to diversify Egyptian cropping systems under semi-arid conditions. However, genotype × environment × management interactions remain poorly characterized for common ( F. esculentum ) and Tartary ( F. tataricum ) buckwheat in Egypt. Methods Field experiments were conducted over two growing seasons (2018/19–2019/20) at two contrasting northern Egyptian sites: the Belbies city site (clay–sandy, irrigated Nile Delta) and the Sadat city site (sandy–loamy, desert fringe). A three‐factor factorial randomized complete block design (RCBD) with three replicates per site was used to evaluate the species (Common vs. Tartary), location (Belbies vs. Sadat), and sowing date (mid-November, mid-January, and mid-March). Vegetative traits (height, branch number, internode number, leaf number, fresh biomass) and productivity parameters (seed count, seed weight, yield) were measured on ten plants and in three 1 m 2 quadrats per plot. Two‐step ANOVA (species‐specific two‐way followed by combined three‐way) and LSD mean separation were applied (α = 0.05). Results Three‐way interactions among species, location, and sowing date were highly significant for all traits (p < 0.001), explaining 18–32% of the variance. Tartary buckwheat outperformed common buckwheat across both sites and seasons, exhibiting greater vegetative vigor and reproductive resilience. At Belbies, mid-March sowing of F. tataricum resulted in the highest grain yields (947 ± 22 kg ha ⁻ ¹ in 2018/19; 997 ± 25 kg ha ⁻ ¹ in 2019/20), whereas common buckwheat yields peaked at mid-November sowing (558 ± 19 and 491 ± 18 kg ha ⁻ ¹, respectively). At Sadat, yields were lower for both species but remained consistently greater for F. tataricum on all sowing dates. Compared with F. tataricum , F. esculentum performed worse under later sowing and desert-fringe conditions. Conclusions Tartary buckwheat presented greater growth and yield than did common buckwheat across the two sites and sowing windows tested. Within Belbies (clay–sandy), mid-March sowing resulted in the highest F. tataricum yields; at Sadat (sandy–loamy), yields were lower across dates. These results indicate that F. tataricum is a promising candidate for Egyptian agroecosystems, with location- and date-specific performance.